Lived experience of State-sponsored intra-national overseas therapeutic mobility for stem cell transplantation - Franchina, Loreley; Sarradon-Eck, Aline; Arnault, Yolande; Le Corroller, Anne-Gaëlle; Zunic, Patricia; Marino, Patricia (Social science & medicine, 2022)
This article focuses on the lived experience of patients with haematological cancer who were transferred from La Réunion (a French overseas Department) to mainland France to undergo allogeneic haematopoietic stem cell transplantation (allo-HSCT). Based on a qualitative study conducted between February 2020 and January 2021 with allo-HSCT recipients, their family caregivers and healthcare professionals, we examined the social, economic and cultural factors shaping the patients' complex experience. We have called this kind of State-sponsored intra-national medical transfer “overseas therapeutic mobility”. The patients' experience of this therapeutic journey beyond their geographical and cultural frontiers has some similarities with transnational therapeutic mobility. Overseas therapeutic mobility to undergo highly technical treatment requires considerable logistic efforts and mobility skills. The remoteness of their families and their affective and cultural environment give mobile patients a feeling of disorientation and causes them much social suffering. The two-fold condition of being a sick person with a possibly lethal disease and being treated overseas can be regarded as a double ordeal. In addition, the unfunded costs place a heavy burden on the patients and those whose families have limited resources. This study points to the cleavages which occur between post-colonial overseas regions and mainland France, and the territorial inequalities existing in patients’ access to specialized treatment due to French policies of healthcare centralization. •The article defines overseas therapeutic mobility.•Explores medical travel for cancer patients inhabiting La Réunion to mainland France.•Offers insight into geographical inequalities due to centralized healthcare politics.•Emphasizes the risk of impoverishment on patients and their families.•Stresses mobility skills and spatial capital.